2020
DOI: 10.1002/ange.201914649
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Periodically Ordered Mesoporosity in Palladium Membranes Enables Exceptional Enhancement of Intrinsic Electrocatalytic Activity for Formic Acid Oxidation

Abstract: Developing superior electrocatalysts for formic acid oxidation (FAO) is the most crucial step in commercializing direct formic acid fuel cells. Herein, we electrodeposited palladium membranes with periodically ordered mesoporosity obtained by asymmetrically replicating the bicontinuous cubic phase structure of a lyotropic liquid‐crystal template. The Pd membrane with the largest periodicity and highest degree of order delivered up to 90.5 m2 g−1 of electrochemical active surface area and 3.34 A mg−1 electrocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
(64 reference statements)
0
20
0
Order By: Relevance
“…Accordingly, its MA approaches 27.25 A•mg −1 , higher than most reported activities of Pd-based electrocatalysts by more than one order of magnitude (Fig. 4(d) and Table S8 in the ESM) [24,[36][37][38][39][40][44][45][46][47][48][49]. These performances also compare favorably to those of single-atom catalysts (such as Ir and Rh) reported recently [42,43], which can be attributed to the unique structural advantages of NPG and their interaction with surface PdHCN.…”
Section: Faor Activities Of Npg-pd and Npg-pd-au Electrodesmentioning
confidence: 48%
“…Accordingly, its MA approaches 27.25 A•mg −1 , higher than most reported activities of Pd-based electrocatalysts by more than one order of magnitude (Fig. 4(d) and Table S8 in the ESM) [24,[36][37][38][39][40][44][45][46][47][48][49]. These performances also compare favorably to those of single-atom catalysts (such as Ir and Rh) reported recently [42,43], which can be attributed to the unique structural advantages of NPG and their interaction with surface PdHCN.…”
Section: Faor Activities Of Npg-pd and Npg-pd-au Electrodesmentioning
confidence: 48%
“…The development of the active anode catalysts for the oxidation of formic acid plays an important role in the DFAFCs' technologies. Nowadays, compared with Pt, Pd-based catalysts are considered as a good candidate for anode catalysts because of their high power density and anti-poisoning ability [3,4]. However, the high cost and the low stability of Pd-based catalysts limit their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al reported the synthesis of electrodeposited Pd membranes with periodically ordered mesoporosity (Figure 4a), which delivered a high ECSA of 90.5 m 2 g −1 and a peak gravimetric current density of 3340 mA mg −1 (7.8 times higher than Pd/C). When tested in a passive fuel cell setup, the catalyst delivered a power density of 24.7 mW cm −2 at room temperature (Ding et al, 2020). Cao et al reported the synthesis of ordered mesoporous Pt nanocubes, where small Pt nanoparticles (5 nm) were found to act as building blocks to form mesoporous crystalline Pt nanocubes by an oriented attachment mechanism (Figure 4b).…”
Section: Anode Electrocatalystsmentioning
confidence: 99%